Pelatihan Optimalisasi Sumber Dan Bahan Ajar Online Sebagai Penunjang Pembelajaran Bagi Anak Asuh Panti Asuhan Arridho - Indah Purnamasari; Abdul Rahman Kadafi; Ishak Kholil; Tuslaela Tuslaela; Sri Rusiyati (TRIDHARMADIMAS: Jurnal Pengabdian Kepada Masyarakat Jayakarta, 2021)
In accordance with the decision of the Minister of Education and Culture of the Republic of Indonesia regarding Circular Letter Number 4 of 2020 concerning the Implementation of Education Policies in the Emergency Period for the Spread of Covid-19 where the Learning from Home Process is carried out through online / distance learning. In its implementation, the online learning process raises new problems including the location of teachers and students being separated when carrying out learning, making teachers unable to directly monitor student activities during the learning process and some of the students have difficulty in accessing, obtaining learning resources and media. to support understanding of the material being studied. Various initiatives were taken to ensure that learning activities continued even in the absence of face-to-face sessions. Technology, more specifically the internet, smartphones, and laptops are now widely used to support distance learning. In order to meet the needs of participants' understanding of learning resources, it is deemed necessary to have training on Optimizing Online Teaching Resources and Materials as Learning Support for Ar Ridho Orphanage Fosters who are able to provide explanations and understanding of how to get learning resources by utilizing online media. The purpose of this training is that it is hoped that the training participants consisting of students will be able to add various reference sources and teaching materials needed and make it easier for them to understand learning materials and use them to support the online learning process.